2018
DOI: 10.1021/acssuschemeng.8b03729
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Dibromide as an Efficient Sensitizer for Photooxidation of Sulfides

Abstract: Flavin derivatives (FLs) are the building blocks and functional groups within many enzymes that absorb strongly in the visible light region and are redox cofactors in a large number of biological processes. We directly attached Br atoms into the conjugated framework of FL to afford FL dibromide (DBFL) and expected the heavy atom effect of Br to facilitate the intersystem crossing of excited FLs to reach the triplet states for efficient sensitization of O2. Compared with FL (ε = 1.01 × 104 M–1 cm–1 at 441 nm),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(73 citation statements)
references
References 72 publications
7
66
0
Order By: Relevance
“…[11] Fore xamples,r iboflavin tetraacetate (RFT) is ar eadily available compound with an oxidation potential of + 1.67 V( vs.S CE) upon photoirradiation (n max = 440 nm). This characteristic has allowed RFT and its derivatives to function as photocatalysts in the aerobic oxidation of benzylic C À Hb onds, [12] benzyl alcohols, [13] benzyl amines, [14] sulfides, [15] and carboxylic acids [16] using O 2 as the terminal oxidant. Nonetheless,t he scope of flavin catalysis is limited by the oxidation potential of the photoexcited state.T he substrates suitable for this reaction system are thus confined primarily to those with electron-releasing substituents that can stabilize the key radical or radical cation intermediates (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…[11] Fore xamples,r iboflavin tetraacetate (RFT) is ar eadily available compound with an oxidation potential of + 1.67 V( vs.S CE) upon photoirradiation (n max = 440 nm). This characteristic has allowed RFT and its derivatives to function as photocatalysts in the aerobic oxidation of benzylic C À Hb onds, [12] benzyl alcohols, [13] benzyl amines, [14] sulfides, [15] and carboxylic acids [16] using O 2 as the terminal oxidant. Nonetheless,t he scope of flavin catalysis is limited by the oxidation potential of the photoexcited state.T he substrates suitable for this reaction system are thus confined primarily to those with electron-releasing substituents that can stabilize the key radical or radical cation intermediates (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…[11] Fore xamples,r iboflavin tetraacetate (RFT) is ar eadily available compound with an oxidation potential of + 1.67 V( vs.S CE) upon photoirradiation (n max = 440 nm). This characteristic has allowed RFT and its derivatives to function as photocatalysts in the aerobic oxidation of benzylic C À Hb onds, [12] benzyl alcohols, [13] benzyl amines, [14] sulfides, [15] and carboxylic acids [16] using O 2 as the terminal oxidant. Nonetheless,t he scope of flavin catalysis is limited by the oxidation potential of the photoexcited state.T he substrates suitable for this reaction system are thus confined primarily to those with electron-releasing substituents that can stabilize the key radical or radical cation intermediates (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were made by Zhao et al who reported the C7,C8-dibrominated flavin 30, again with the intention to benefit from the heavy atom effect (Scheme 25B). 70 The authors could show the superior catalytic activity of Scheme 25 Designed flavin catalysts with iodo (A) and bromo (B) substitution, which both benefit from the heavy atom effect.…”
Section: Scheme 24mentioning
confidence: 99%
“…Similar observations were made by Zhao, Guo, and co-workers who reported the C7,C8-dibrominated flavin 30, again with the intention to benefit from the heavy atom effect (Figure 7B). 70 They showed that the superior catalytic…”
Section: C6-c9-modificationmentioning
confidence: 99%